Arca-Arca Wisnu Di Asia Tenggara (Abad Ke 4-8 M) - Sri Utami Ferdinandus (Berkala Arkeologi, 1995)
With the entry of Hindu-Buddhist influence in Southeast Asia at the beginning of AD appeared Hindu kingdoms in Southeast Asia in the 5th century A.D. With the advent of Hindu influence and the establishment of Hindu kingdoms in Southeast Asia such as Java, Kalimantan (Taruma, and Kutai ), Pagan (Burma) and Funan (Cambodia) are found relics of statues and sacred buildings scattered in Southeast Asia.